Combination of narrow bipolar pulses and attempted leaders in Melaka, Malaysia - Isa, Nur Asyiqin Binti Mohd; Baharudin, Zikri Abadi; Daud, Izdihartun Najihah Binti Ahmad; Zainuddin, Hidayat (Institute of Advanced Engineering and Science, 2022)
This paper presents the characteristic of the positive attempted leaders preceded by positive narrow bipolar pulses (NPBPs). Attempted leaders are the preliminary breakdown process with no subsequent event (return stroke). On the other hand, narrow bipolar pulse is the lightning event commonly isolated and produces a strong electromagnetic field (in a short period). Attempted leaders hardly occurred in the tropics, and the preceding of the NBP (the combination) should be considered unique. In this present study, we found four samples in which the arithmetic means of duration of NPBPs pulse was 32.19 µs, with separation between the positive attempted leader was 1.86 ms apart. For the positive attempted leader, the arithmetic means of the whole pulse train, individual pulse and interval pulse of positive attempted leaders were 3.47 ms, 29.66 µs and 486.53 µs, respectively. The pulse train in this study seems to fade out fast compared to the isolated positive attempted leader pulse train. Next, the NPBP's pulse duration in this study shows well in agreement with the type of isolated NPBPs indicates that the association does not affect its pulse duration characteristic already present in the title.